Scientific reasoning skills (SRS): Predictor to the student’s problem-solving in the biology classroom? - Maisuna Kundariati; Laila Maghfiroh; Sri Endah Indriwati; Fatchur Rohman; Bagus Priambodo; Noor Azean Atan (Biosfer: Jurnal Pendidikan Biologi, 2021)
Scientific reasoning and problem-solving have become primary interests in 21st-century education. These skills have an essential role in preparing students to face global competition. This study aims to determine the correlation between scientific reasoning and problem-solving skills of biology students in animal classification and whether scientific reasoning can be used to predict problem-solving skills. The participants were 56 undergraduate students of Biology Education. The scientific reasoning and problem-solving skills of students were assessed with the pre and post-test. A simple linear regression test using the SPSS 16.0 was applied in data analysis. The results showed a p-value of 0.00 < 0.05, so there is a correlation between scientific reasoning and argumentation skills. R-value indicates 0.523, which means a strong correlation. The contribution of scientific reasoning to argumentation skills was 27.3%, while other variables explained the rest.